Management of Root Rot of Jatropha Caused by Rhizoctonia bataticola with Plant Growth Promoting Rhizobacteria - Kumar, S.; Sharma, Sushil; Saharan, H. S.; Deswal, R. P. (Indian Forester, 2012)
The root rot of Jatropha caused by Rhizoctonia bataticola is an important disease. An experiment was conducted invitroand in vivoto evaluate the effect of plant growth promoting bacteria against R. bataticola. The study revealed that Pseudomonas fluorescens caused the maximum growth inhibition (48.9%) followed by Pseudomonas maltophilia (46.7%) and Bacillus subtilis (38.9%). The seed germination percentage improved substantially in all the treatments involving PGPRs. Among different co-inoculations of PGPRs and pathogen, minimum pre-emergence mortality (31.1%) and post-emergence mortality (9.7%) and maximum seedling survival (40.78%)was observed with P. fluorescens.